Solusi Guru Mapel PAI dalam Mengurangi Faktor Kesulitan Belajar Siswa - Wardhani, Sayekti Putri; Maryanto, Maryanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
Islamic Religious Education at SMK Batik Sakti Kebumen. This research is qualitative research which ams to determine the factors that cause students’ learning difficulties in learning PAI based on Kurikulum Merdeka at SMK Batik Sakti 1 Kebumen. Data collection techniques in this research used observation, interview and documentation techniques. The research was carried out by intervieweinng teachers with the aim of finding out students who had learning difficulties in class X PAI subjects, then interviewing these students about the causes of PAI learning difficulties in terms of internal and external factors. Data analysis thecniques use data condensation, data presentation, and conclusion verification. The results of this research that internal solution for PAI teachers in reducig learning difficulties for class. Meanwhile, the teachers external solution in reducing students’ learning difficulties i that the teacher creates interesting learning media, diagnoses students’ learning difficulties, provides learning motivation, and pays more attention to students who experience learning difficulties.